Amanitins and their development as a payload for antibody-drug conjugates. (December 2018) - Pahl, Andreas; Lutz, Christian; Hechler, Torsten
Graphical abstract: Abstract : Amanitin-based ADCs represent a new class of ADCs using a novel mode of action. This payload introduces a novel mode of action into oncology therapy, the inhibition of RNA Polymerase II. The high potency of the toxin leads to highly efficacious ADCs. The development of the technology around this toxin will be described. These developments support the clinical development of amanitin-based ADCs by using a toxin with a new mode of action and with a favorable therapeutic index. HDP-101 is an Amanitin based ADC directed against BCMA and will be advancing to the clinical phase in 2019.